NEW EASTERN CAPE TOURISM LEGISLATION - PHG Vrancken (Obiter, 2022)
At the end of 2003, the Eastern Cape Province brought its tourism legislation up to date with the recent relevant legislative developments in the country. After outlining the context of the reform, this article compares the new legislation with the legislation that it repeals and explains the innovations brought about by the new legislation, concluding by pointing out the challenge of implementation.